AKTIVITAS ANTIOKSIDAN DAN EFEK SITOTOKSIK EKSTRAK KOLA (COLA NITIDA) PADA KULTER SEL KANKER HATI (HEPG-2) - Endrini, Susi; Marsiati, Himmi; J, Suherman; O, Fauziah; R, Asmah (Jurnal Kedokteran YARSI, 2009)
Liver cancer is one among cancers with increasing incidence in the world. Cola fruit (Cola nitida) is a fruit that is rich in properties and has been known since the Dutch colonial era. This fruit contains ingredients such as those contained in tea and chocolate such as methylxanthine and its derivatives. This study aims to determine the content of antioxidants and cytotoxic effects of cola fruit extracts obtained from Indonesia and Malaysia on liver cancer cell lines. Antioxidant content of fruit extracts of cola was assessed using DPPH (2,2-diphenyl-2-picrylhydrazyl hydrate) and cytotoxic effects were studied using MTT (3 - (4,5-Dimethylthiazol-2-Yl)diphenyltetrazolium bromide -2.5) on human liver cancer cell lines (HepG2). The results showed that cola fruit from Malaysia contained high antioxidant with the IC50 value of 37.2 ?g/mL whereas IC50 of value of its Indonesia?s cola fruit was 66.0 ug / mL. The similar results have been shown in the cytotoxic test using HepG-2 liver cancer cell lines. Malaysia?s cola fruit extract has a smaller IC50 value of 6.5 ?g / mL while the fruit extract of Indonesia?s cola showed IC50 value of 39.5 ?g / mL. These values indicates that the fruit extract of cola is a potential anticancer activities especially on liver cancer. Further studies are required to clarify this hypothesis.